Waterproof and moistureproof cable with simple layer structure

By adding fluororesin and cationic doped resin to the sheath layer of the cable, the hydrophobicity and charge-attracting effect are used to solve the problem that the cable is susceptible to moisture invasion in humid environments, achieving efficient waterproofing performance improvement, and simplifying the Cable structure.

CN119446643APending Publication Date: 2025-02-14江苏渠成电缆科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411795059.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Existing cables are susceptible to moisture invasion in humid environments, resulting in short circuits of electrical circuits, aging of insulation, and failure of electrical equipment. Special waterproof compartments are required to be installed in the cables to improve waterproof performance.

Method used

By adding fluororesin and cationic doped resin to the outermost sheath layer of the cable, the hydrophobicity of the fluorine segment and the charge attraction effect of the cationic doped resin are used to improve the waterproof performance of the sheath layer so that it does not require special settings waterproof compartment.

Benefits of technology

It realizes the normal operation of the cable in harsh environments, improves the waterproof and moisture-proof effect of the cable, and simplifies the cable structure and processing process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119446643A_ABST
    Figure CN119446643A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of wires and cables, and particularly relates to a waterproof and moistureproof cable with a simple layer structure, which comprises more than two conductor wire cores, each conductor wire core is tightly wrapped by an insulating layer, and the insulating layer is coaxially and tightly wrapped by a shielding layer. All the conductor wire cores wrapped with the insulating layers and the shielding layers are twisted together and then are tightly wrapped with a non-woven fabric layer, the non-woven fabric layer is tightly wrapped with a waterproof sheath layer, the waterproof sheath layer comprises polypropylene, a POE thermoplastic elastomer, fluororesin, cation doped resin, a plasticizer, an antioxidant and a lubricant, and the resin material of the sheath layer is modified, so that the waterproof performance of the cable is improved, and the service life of the cable is prolonged. The sheath layer is endowed with an ideal waterproof effect, a special waterproof interlayer does not need to be arranged in the cable, and the cable structure and the processing procedure are simplified.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electric wires and cables, and in particular relates to a waterproof and moisture-proof cable with a simple layer structure. Background Art

[0002] Cables are a key component of the power system, but they are susceptible to moisture intrusion in a humid environment, leading to problems such as electrical line short circuits, insulation aging, and electrical equipment failures, which will not only affect the normal operation of the equipment, but may also cause equipment damage and even cause serious consequences such as fires. Therefore, the waterproof and moisture-proof performance of cables directly affects the stability and safety of the power system. Effective waterproof measures can reduce the corrosion and aging of cables caused by moisture, ensure that cables can still work normally in various harsh environments, and ensure the stable operation of the power system. For example, a special waterproof barrier layer is set in the cable, and the cable sheath material is hydrophobically modified. Among them, the fluorine segment has good hydrophobicity, and the fluorine segment has a lower surface free energy than other segments. After being added to the matrix as a modified resin (especially when the amount of fluorine resin added is small), it is easy to migrate to the surface of the matrix during the curing process, thereby further reducing the surface energy after enrichment on the surface of the matrix, playing a waterproof and water-repellent role.

[0003] However, the above-mentioned migration behavior of fluorine segments in the matrix is ​​spontaneous after all. From a microscopic analysis, some fluorine segments have effectively migrated, while the migration degree of a considerable number of fluorine segments is very limited. Therefore, if some measures can be taken to further drive the migration ability of fluorine segments, it is expected to further improve the waterproof and moisture-proof effect of the cable without setting a special waterproof barrier in the cable. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a waterproof and moisture-proof cable with a simple layer structure, the waterproof and moisture-proof cable comprises more than two conductor cores, each conductor core is tightly wrapped with an insulating layer, and a shielding layer is tightly wrapped outside the insulating layer, and all the conductor cores wrapped with the insulating layer and the shielding layer are twisted together as a whole, and are tightly wrapped by a non-woven fabric layer, and a waterproof sheath layer is tightly wrapped outside the non-woven fabric layer.

[0005] The waterproof sheath layer is calculated by weight and includes 100 parts of polypropylene, 10-15 parts of POE thermoplastic elastomer, 10-20 parts of fluororesin, 5-10 parts of cationic doped resin, 3-8 parts of plasticizer, 1-2 parts of antioxidant, and 1-3 parts of lubricant.

[0006] As a preferred embodiment: the conductor core is formed by twisting a number of round copper wires;

[0007] The aluminum-plastic tape is evenly wrapped around the insulation layer as a shielding layer;

[0008] The non-woven fabric is evenly wrapped around the surface of the conductor core which is sequentially wrapped with an insulating layer and a shielding layer and twisted together to serve as a non-woven fabric layer.

[0009] Preferably, the gaps between the conductor cores wrapped with the insulating layer and the shielding layer on the inner side of the non-woven fabric layer are filled with filling ropes.

[0010] Preferably, the fluororesin is polyvinylidene fluoride.

[0011] Preferably, the cationic doped resin is polymerized from butyl acrylate, styrene and a cationic monomer, wherein the cationic monomer is methacryloyloxyethyltrimethylammonium chloride, and the weight ratio of butyl acrylate, styrene and the cationic monomer is 40-60:40-60:10-15.

[0012] Further: the preparation operation of the cation-doped resin is:

[0013] (1) After the cationic monomer is fully dispersed and dissolved in water, butyl acrylate and styrene are added dropwise thereto under stirring. After the addition is completed, stirring is continued until the emulsification is fully emulsified to obtain an emulsion, and two-thirds of the emulsion is taken out for subsequent addition;

[0014] (2) Under condensation reflux, the remaining one third of the emulsion in step (1) is heated in a water bath to 70-80°C under stirring, and an initiator solution is added dropwise thereto. After a period of dropwise addition, the other two thirds of the emulsion taken out in step (1) are added dropwise thereto. After the addition of the initiator solution and the emulsion is completed, the reaction is continued at a temperature of 25°C and then cooled to room temperature (25°C, the same below). The obtained reaction system is centrifuged and the obtained polymer is fully washed and dried.

[0015] Furthermore: in step (1), the cationic monomer is dispersed and dissolved in water at a mass percentage of 1% to 3%.

[0016] Furthermore, in step (2), the initiator solution is an aqueous solution having a mass concentration of ammonium persulfate of 1% to 5% and a mass concentration of anhydrous sodium sulfite of 1% to 5%.

[0017] Preferably, the plasticizer is dibutyl phthalate or dioctyl phthalate.

[0018] Preferably, the antioxidant is antioxidant 1010 or antioxidant 168.

[0019] Preferably, the lubricant is zinc stearate or calcium stearate.

[0020] As a preferred embodiment: the processing method of the cable includes: melting the insulating layer masterbatch in an extruder, extruding it on the outer surface of the conductor core, and cooling to form an insulating layer tightly wrapped on the conductor core; wrapping the aluminum-plastic tape evenly and tightly on the insulating layer as a shielding layer; all the conductor cores wrapped with the insulating layer and the shielding layer and the filling ropes used to fill the gaps are parallel to each other and then twisted together, and then the conductor cores and the filling ropes twisted together are uniformly wrapped with non-woven fabric as a whole to form a non-woven fabric layer; melting the masterbatch for preparing the waterproof sheath layer in an extruder, extruding it on the non-woven fabric layer, and cooling to form a waterproof sheath layer tightly wrapped on the non-woven fabric layer,

[0021] The filling rope is fluffy and elastic in its natural state. Therefore, during the concentrated twisting and non-woven fabric wrapping process, the filling rope is further squeezed by the conductor core or the non-woven fabric, and thus the gaps can be basically filled.

[0022] The beneficial effect of the present invention is that: this scheme gives the sheath layer an ideal waterproof effect by modifying the resin material of the outermost sheath layer of the cable, and there is no need to set a special waterproof barrier in the cable, which simplifies the cable structure and processing procedures. Specifically, after adding fluororesin to the polypropylene matrix, the fluorine chain segment has a tendency to migrate and aggregate to the surface of the casing during the processing, which reduces the surface energy of the casing and improves the water repellency. On this basis, the added cation-doped resin contains a considerable number of benzene rings, which makes the compatibility between the cation-doped resin and the matrix poor. After melt extrusion and blending, the cation-doped resin will migrate and precipitate relatively close to the sheath surface to a certain extent, so that a certain amount of cations are enriched near the surface of the sheath and it carries a positive charge. The positive charge forms a charge attraction effect with the negatively charged fluorine atoms in the fluorine-containing chain segment, thereby further improving the migration and proximity of the fluorine-containing chain segment in the sheath to the sheath surface, thereby further improving the waterproof effect of the sheath surface and inhibiting water penetration. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 It is a schematic cross-sectional view of the internal layer structure of the waterproof and moisture-proof cable of the present invention;

[0024] Figure 2 This is a basic structural diagram of a device for performing a waterproof test on a cable in the embodiment of the present invention.

[0025] Among them, 1 is the conductor core, 2 is the insulation layer, 3 is the shielding layer, 4 is the non-woven fabric layer, 5 is the filling rope, 6 is the waterproof sheath layer, 10 is the sample, 20 is the water storage tank (made of glass), 21 is the tank cover, 22 is the gripper, 30 is the rubber elastic sealing plug, and 40 is the humidity sensor. DETAILED DESCRIPTION

[0026] Example 1

[0027] Preparation of cation-doped resin:

[0028] (1) Dispersing and dissolving 3 parts by weight of methacryloyloxyethyl trimethylammonium chloride in 150 parts by weight of water at room temperature, 8 parts by weight of butyl acrylate and 12 parts by weight of styrene were added dropwise thereto under stirring. After the addition was completed, stirring was continued until the mixture was fully emulsified to obtain an emulsion. About two-thirds of the emulsion was taken out for subsequent addition;

[0029] (2) Under condensation reflux, the remaining about one third of the emulsion in step (1) is heated to 75° C. in a water bath under stirring, and an initiator solution obtained by dissolving 0.2 parts by weight of ammonium persulfate and 0.2 parts by weight of anhydrous sodium sulfite in 10 parts by weight of water is added dropwise thereto. The initiator solution is added dropwise until the bottom of the emulsion turns blue, and then about two thirds of the emulsion taken out in step (1) is added dropwise thereto at the same time. During this period, the temperature of the reaction system is controlled at 75-80° C. After the addition of the initiator solution and the emulsion is completed, the reaction is continued at a temperature of 75 to 80° C. for 20 minutes, and then the temperature is lowered to room temperature. The obtained reaction system is centrifuged, and the obtained polymer is fully washed with ethanol and then dried at 80° C.

[0030] Processing and preparation of waterproof jacket layer masterbatch:

[0031] Calculated by weight, 100 parts of polypropylene (Yanshan Petrochemical 1396D, the same below), 12 parts of POE thermoplastic elastomer (Dow 8100, the same below), 17 parts of polyvinylidene fluoride (710, the same below), 6 parts of the cationic doped resin prepared above in this embodiment, 5 parts of dioctyl phthalate, 1.5 parts of antioxidant 1010, and 1.5 parts of zinc stearate were added to a high-speed mixer and stirred at a speed of 1500r / min for 30 minutes. The resulting mixture was added to a twin-screw extruder at 170-190°C for blending, extrusion, and granulation.

[0032] Processing and preparation of waterproof and moisture-proof cables:

[0033] After conventional insulating layer masterbatch is melted in an extruder, it is extruded onto the outer surface of the conductor core, and after cooling, an insulating layer coaxially and tightly wrapped on the conductor core is formed; an aluminum-plastic tape is evenly and tightly wrapped on the insulating layer to form a shielding layer coaxially arranged with the insulating layer; 7 conductor cores wrapped with insulating layer and shielding layer as mentioned above and several filling ropes used to fill the gaps between the conductor cores are matched and concentrated together in parallel (wherein, the conductor cores are distributed in a circular shape with one core inside and six cores are evenly and tightly arranged on the outside) and then twisted together, and then the twisted conductor cores and filling ropes are taken as a whole, and non-woven fabric is evenly and tightly wrapped on them to form a non-woven fabric layer coaxially arranged with the whole; the waterproof jacket layer masterbatch prepared in this embodiment is re-melted and extruded in an extruder at 170-190°C and evenly extruded onto the non-woven fabric layer, and after cooling, a waterproof jacket layer coaxially and tightly wrapped with the non-woven fabric layer is formed (after the waterproof jacket layer is formed, the thickness is about 2mm, the same below). The internal layer structure of the prepared cable is as shown in the attached figure. Figure 1 shown.

[0034] Example 2

[0035] Processing and preparation of waterproof jacket layer masterbatch:

[0036] Calculated by weight, 100 parts of polypropylene, 10 parts of POE thermoplastic elastomer, 20 parts of polyvinylidene fluoride, 8 parts of cationic doped resin (prepared in Example 1), 8 parts of dioctyl phthalate, 2 parts of antioxidant 168, and 1.5 parts of calcium stearate were added to a high-speed mixer and stirred at a speed of 900 r / min for 60 minutes. The resulting mixture was added to a twin-screw extruder for blending, extrusion, and granulation at 170-190°C.

[0037] Processing and preparation of waterproof and moisture-proof cable (wherein, only the waterproof sheath layer masterbatch is prepared in this embodiment, and the other components and operations are the same as in Example 1):

[0038] After conventional insulating layer masterbatch is melted in an extruder, it is extruded onto the outer surface of the conductor core, and after cooling, an insulating layer coaxially and tightly wrapped on the conductor core is formed; an aluminum-plastic tape is evenly and tightly wrapped on the insulating layer to form a shielding layer coaxially arranged with the insulating layer; 7 conductor cores wrapped with insulating layer and shielding layer as mentioned above and several filling ropes used to fill the gaps between the conductor cores are assembled together in parallel (wherein the conductor cores are distributed in a circular shape with one core inside and six cores are evenly and tightly arranged on the outside) and then twisted together, and then the twisted conductor cores and filling ropes are taken as a whole, and non-woven fabric is evenly and tightly wrapped thereon to form a non-woven fabric layer coaxially arranged with the whole; the waterproof sheath layer masterbatch prepared in this embodiment is re-melted and extruded in an extruder at 170-190°C and evenly extruded onto the non-woven fabric layer, and after cooling, a waterproof sheath layer coaxially and tightly wrapped with the non-woven fabric layer is formed. The internal layer structure of the prepared cable is shown in the attached figure. Figure 1 shown.

[0039] Example 3

[0040] Processing and preparation of waterproof jacket layer masterbatch:

[0041] Calculated by weight, 100 parts of polypropylene, 15 parts of POE thermoplastic elastomer, 10 parts of polyvinylidene fluoride, 5 parts of cationic doped resin (prepared in Example 1), 5 parts of dioctyl phthalate, 2 parts of antioxidant 1010, and 1.5 parts of calcium stearate are added to a high-speed mixer and stirred at a speed of 1200r / min for 45 minutes. The resulting mixture is added to a twin-screw extruder at 170-190°C for blending, extrusion, and granulation.

[0042] Processing and preparation of waterproof and moisture-proof cable (wherein, only the waterproof sheath layer masterbatch is prepared in this embodiment, and the other components and operations are the same as in Example 1):

[0043] After conventional insulating layer masterbatch is melted in an extruder, it is extruded onto the outer surface of the conductor core, and after cooling, an insulating layer coaxially and tightly wrapped on the conductor core is formed; an aluminum-plastic tape is evenly and tightly wrapped on the insulating layer to form a shielding layer coaxially arranged with the insulating layer; 7 conductor cores wrapped with insulating layer and shielding layer as mentioned above and several filling ropes used to fill the gaps between the conductor cores are assembled together in parallel (wherein the conductor cores are distributed in a circular shape with one core inside and six cores are evenly and tightly arranged on the outside) and then twisted together, and then the twisted conductor cores and filling ropes are taken as a whole, and non-woven fabric is evenly and tightly wrapped thereon to form a non-woven fabric layer coaxially arranged with the whole; the waterproof sheath layer masterbatch prepared in this embodiment is re-melted and extruded in an extruder at 170-190°C and evenly extruded onto the non-woven fabric layer, and after cooling, a waterproof sheath layer coaxially and tightly wrapped with the non-woven fabric layer is formed. The internal layer structure of the prepared cable is shown in the attached figure. Figure 1 shown.

[0044] Comparative Example 1

[0045] Processing and preparation of waterproof jacket layer masterbatch:

[0046] The "6 parts of cationic doped resin" in the waterproof sheath layer is replaced by an equal amount of base polypropylene resin, and the remaining components and operations are the same as those in Example 1:

[0047] Calculated by weight, 106 parts of polypropylene, 12 parts of POE thermoplastic elastomer, 17 parts of polyvinylidene fluoride, 5 parts of dioctyl phthalate, 1.5 parts of antioxidant 1010, and 1.5 parts of zinc stearate are added to a high-speed mixer and stirred at a speed of 1500r / min for 30 minutes. The resulting mixture is added to a twin-screw extruder for blending, extrusion, and granulation at 170-190°C.

[0048] Processing and preparation of waterproof and moisture-proof cable (wherein, only the waterproof sheath layer masterbatch is prepared in this comparative example, and the other components and operations are the same as in Example 1):

[0049] After conventional insulating layer masterbatch is melted in an extruder, it is extruded onto the outer surface of the conductor core, and after cooling, an insulating layer coaxially and tightly wrapped on the conductor core is formed; an aluminum-plastic tape is evenly and tightly wrapped on the insulating layer to form a shielding layer coaxially arranged with the insulating layer; 7 conductor cores wrapped with insulating layer and shielding layer as mentioned above and several filling ropes used to fill the gaps between the conductor cores are matched and concentrated together in parallel (wherein the conductor cores are distributed in a circular shape with one core inside and six cores are evenly and tightly arranged on the outside) and then twisted together, and then the twisted conductor cores and filling ropes are taken as a whole, and non-woven fabric is evenly and tightly wrapped thereon to form a non-woven fabric layer coaxially arranged with the whole; the waterproof sheath layer masterbatch prepared in this comparative example is re-melted and extruded in an extruder at 170-190°C and evenly extruded onto the non-woven fabric layer, and after cooling, a waterproof sheath layer coaxially and tightly wrapped with the non-woven fabric layer is formed. The internal layer structure of the prepared cable is shown in the attached figure. Figure 1 shown.

[0050] Comparative Example 2

[0051] Processing and preparation of waterproof jacket layer masterbatch:

[0052] The "polyvinylidene fluoride" in the waterproof sheath layer is replaced by an equal amount of base polypropylene resin, and the remaining components and operations are the same as those in Example 1:

[0053] Calculated by weight, 117 parts of polypropylene, 12 parts of POE thermoplastic elastomer, 6 parts of cationic doped resin (prepared in Example 1), 5 parts of dioctyl phthalate, 1.5 parts of antioxidant 1010, and 1.5 parts of zinc stearate were added to a high-speed mixer and stirred at a speed of 1500r / min for 30 minutes. The resulting mixture was added to a twin-screw extruder at 170-190°C for blending, extrusion, and granulation.

[0054] Processing and preparation of waterproof and moisture-proof cable (wherein, only the waterproof sheath layer masterbatch is prepared in this comparative example, and the other components and operations are the same as in Example 1):

[0055] After conventional insulating layer masterbatch is melted in an extruder, it is extruded onto the outer surface of the conductor core, and after cooling, an insulating layer coaxially and tightly wrapped on the conductor core is formed; an aluminum-plastic tape is evenly and tightly wrapped on the insulating layer to form a shielding layer coaxially arranged with the insulating layer; 7 conductor cores wrapped with insulating layer and shielding layer as mentioned above and several filling ropes used to fill the gaps between the conductor cores are matched and concentrated together in parallel (wherein the conductor cores are distributed in a circular shape with one core inside and six cores are evenly and tightly arranged on the outside) and then twisted together, and then the twisted conductor cores and filling ropes are taken as a whole, and non-woven fabric is evenly and tightly wrapped thereon to form a non-woven fabric layer coaxially arranged with the whole; the waterproof sheath layer masterbatch prepared in this comparative example is re-melted and extruded in an extruder at 170-190°C and evenly extruded onto the non-woven fabric layer, and after cooling, a waterproof sheath layer coaxially and tightly wrapped with the non-woven fabric layer is formed. The internal layer structure of the prepared cable is shown in the attached figure. Figure 1 shown.

[0056] Comparative Example 3

[0057] Preparation of doped resin:

[0058] The "methacryloyloxyethyl trimethylammonium chloride" in step (1) is replaced with an equal amount of "isomeric tridecanol polyoxyethylene ether (TO-50)", and the remaining components and operations are the same as those in Example 1:

[0059] (1) At room temperature, 3 parts by weight of isomeric tridecanol polyoxyethylene ether is dispersed and dissolved in 150 parts by weight of water, and then 8 parts by weight of butyl acrylate and 12 parts by weight of styrene are added dropwise thereto under stirring. After the addition is completed, stirring is continued until the mixture is fully emulsified to obtain an emulsion, and about two-thirds of the emulsion is taken out for subsequent addition;

[0060] (2) Under condensation reflux, the remaining about one third of the emulsion in step (1) is heated to 75° C. in a water bath under stirring, and an initiator solution obtained by dissolving 0.2 parts by weight of ammonium persulfate and 0.2 parts by weight of anhydrous sodium sulfite in 10 parts by weight of water is added dropwise thereto. The initiator solution is added dropwise until the bottom of the emulsion turns blue, and then about two thirds of the emulsion taken out in step (1) is added dropwise thereto at the same time. During this period, the temperature of the reaction system is controlled at 75-80° C. After the addition of the initiator solution and the emulsion is completed, the reaction is continued at a temperature of 75 to 80° C. for 20 minutes, and then the temperature is lowered to room temperature. The obtained reaction system is centrifuged, and the obtained polymer is fully washed with ethanol and then dried at 80° C.

[0061] Processing and preparation of waterproof jacket layer masterbatch:

[0062] Calculated by weight, 100 parts of polypropylene, 12 parts of POE thermoplastic elastomer, 17 parts of polyvinylidene fluoride, 6 parts of the doped resin prepared above in this comparative example, 5 parts of dioctyl phthalate, 1.5 parts of antioxidant 1010, and 1.5 parts of zinc stearate are added to a high-speed mixer and stirred and mixed at a speed of 1500r / min for 30 minutes. The resulting mixture is added to a twin-screw extruder at 170-190°C for blending, extrusion, and granulation.

[0063] Processing and preparation of waterproof and moisture-proof cable (wherein, only the waterproof sheath layer masterbatch is prepared in this comparative example, and the other components and operations are the same as in Example 1):

[0064] After conventional insulating layer masterbatch is melted in an extruder, it is extruded onto the outer surface of the conductor core, and after cooling, an insulating layer coaxially and tightly wrapped on the conductor core is formed; an aluminum-plastic tape is evenly and tightly wrapped on the insulating layer to form a shielding layer coaxially arranged with the insulating layer; 7 conductor cores wrapped with insulating layer and shielding layer as mentioned above and several filling ropes used to fill the gaps between the conductor cores are matched and concentrated together in parallel (wherein the conductor cores are distributed in a circular shape with one core inside and six cores are evenly and tightly arranged on the outside) and then twisted together, and then the twisted conductor cores and filling ropes are taken as a whole, and non-woven fabric is evenly and tightly wrapped thereon to form a non-woven fabric layer coaxially arranged with the whole; the waterproof sheath layer masterbatch prepared in this comparative example is re-melted and extruded in an extruder at 170-190°C and evenly extruded onto the non-woven fabric layer, and after cooling, a waterproof sheath layer coaxially and tightly wrapped with the non-woven fabric layer is formed. The internal layer structure of the prepared cable is shown in the attached figure. Figure 1 shown.

[0065] Comparative Example 4

[0066] Preparation of cation-doped resin:

[0067] The "8 parts by weight of butyl acrylate and 12 parts by weight of styrene" in step (1) is replaced by "2 parts by weight of butyl acrylate and 18 parts by weight of styrene", and the remaining components and operations are the same as those in Example 1:

[0068] (1) Dispersing and dissolving 3 parts by weight of methacryloyloxyethyl trimethylammonium chloride in 150 parts by weight of water at room temperature, 2 parts by weight of butyl acrylate and 18 parts by weight of styrene are added dropwise under stirring. After completion, stirring is continued until the mixture is fully emulsified to obtain an emulsion. About two-thirds of the emulsion is taken out for subsequent dropping;

[0069] (2) Under condensation reflux, the remaining about one third of the emulsion in step (1) is heated to 75° C. in a water bath under stirring, and an initiator solution obtained by dissolving 0.2 parts by weight of ammonium persulfate and 0.2 parts by weight of anhydrous sodium sulfite in 10 parts by weight of water is added dropwise thereto. The initiator solution is added dropwise until the bottom of the emulsion turns blue, and then about two thirds of the emulsion taken out in step (1) is added dropwise thereto at the same time. During this period, the temperature of the reaction system is controlled at 75-80° C. After the addition of the initiator solution and the emulsion is completed, the reaction is continued at a temperature of 75 to 80° C. for 20 minutes, and then the temperature is lowered to room temperature. The obtained reaction system is centrifuged, and the obtained polymer is fully washed with ethanol and then dried at 80° C.

[0070] Processing and preparation of waterproof jacket layer masterbatch:

[0071] Calculated by weight, 100 parts of polypropylene, 12 parts of POE thermoplastic elastomer, 17 parts of polyvinylidene fluoride, 6 parts of the cationic doped resin prepared above in this comparative example, 5 parts of dioctyl phthalate, 1.5 parts of antioxidant 1010, and 1.5 parts of zinc stearate are added to a high-speed mixer and stirred and mixed at a speed of 1500r / min for 30 minutes. Then, the resulting mixture is added to a twin-screw extruder for blending, extrusion, and granulation at 170-190°C.

[0072] Processing and preparation of waterproof and moisture-proof cable (wherein, only the waterproof sheath layer masterbatch is prepared in this comparative example, and the other components and operations are the same as in Example 1):

[0073] After conventional insulating layer masterbatch is melted in an extruder, it is extruded onto the outer surface of the conductor core, and after cooling, an insulating layer coaxially and tightly wrapped on the conductor core is formed; an aluminum-plastic tape is evenly and tightly wrapped on the insulating layer to form a shielding layer coaxially arranged with the insulating layer; 7 conductor cores wrapped with insulating layer and shielding layer as mentioned above and several filling ropes used to fill the gaps between the conductor cores are matched and concentrated together in parallel (wherein the conductor cores are distributed in a circular shape with one core inside and six cores are evenly and tightly arranged on the outside) and then twisted together, and then the twisted conductor cores and filling ropes are taken as a whole, and non-woven fabric is evenly and tightly wrapped thereon to form a non-woven fabric layer coaxially arranged with the whole; the waterproof sheath layer masterbatch prepared in this comparative example is re-melted and extruded in an extruder at 170-190°C and evenly extruded onto the non-woven fabric layer, and after cooling, a waterproof sheath layer coaxially and tightly wrapped with the non-woven fabric layer is formed. The internal layer structure of the prepared cable is shown in the attached figure. Figure 1 shown.

[0074] Comparative Example 5

[0075] Preparation of cation-doped resin:

[0076] The "8 parts by weight of butyl acrylate and 12 parts by weight of styrene" in step (1) is replaced by "18 parts by weight of butyl acrylate and 2 parts by weight of styrene", and the remaining components and operations are the same as those in Example 1:

[0077] (1) Dispersing and dissolving 3 parts by weight of methacryloyloxyethyl trimethylammonium chloride in 150 parts by weight of water at room temperature, 18 parts by weight of butyl acrylate and 2 parts by weight of styrene were added dropwise thereto under stirring. After the addition was completed, stirring was continued until the mixture was fully emulsified to obtain an emulsion. About two-thirds of the emulsion was taken out for subsequent addition;

[0078] (2) Under condensation reflux, the remaining about one third of the emulsion in step (1) is heated to 75° C. in a water bath under stirring, and an initiator solution obtained by dissolving 0.2 parts by weight of ammonium persulfate and 0.2 parts by weight of anhydrous sodium sulfite in 10 parts by weight of water is added dropwise thereto. The initiator solution is added dropwise until the bottom of the emulsion turns blue, and then about two thirds of the emulsion taken out in step (1) is added dropwise thereto at the same time. During this period, the temperature of the reaction system is controlled at 75-80° C. After the addition of the initiator solution and the emulsion is completed, the reaction is continued at a temperature of 75 to 80° C. for 20 minutes, and then the temperature is lowered to room temperature. The obtained reaction system is centrifuged, and the obtained polymer is fully washed with ethanol and then dried at 80° C.

[0079] Processing and preparation of waterproof jacket layer masterbatch:

[0080] Calculated by weight, 100 parts of polypropylene, 12 parts of POE thermoplastic elastomer, 17 parts of polyvinylidene fluoride, 6 parts of the cationic doped resin prepared above in this comparative example, 5 parts of dioctyl phthalate, 1.5 parts of antioxidant 1010, and 1.5 parts of zinc stearate are added to a high-speed mixer and stirred and mixed at a speed of 1500r / min for 30 minutes. Then, the resulting mixture is added to a twin-screw extruder for blending, extrusion, and granulation at 170-190°C.

[0081] Processing and preparation of waterproof and moisture-proof cable (wherein, only the waterproof sheath layer masterbatch is prepared in this comparative example, and the other components and operations are the same as in Example 1):

[0082] After conventional insulating layer masterbatch is melted in an extruder, it is extruded onto the outer surface of the conductor core, and after cooling, an insulating layer coaxially and tightly wrapped on the conductor core is formed; an aluminum-plastic tape is evenly and tightly wrapped on the insulating layer to form a shielding layer coaxially arranged with the insulating layer; 7 conductor cores wrapped with insulating layer and shielding layer as mentioned above and several filling ropes used to fill the gaps between the conductor cores are matched and concentrated together in parallel (wherein the conductor cores are distributed in a circular shape with one core inside and six cores are evenly and tightly arranged on the outside) and then twisted together, and then the twisted conductor cores and filling ropes are taken as a whole, and non-woven fabric is evenly and tightly wrapped thereon to form a non-woven fabric layer coaxially arranged with the whole; the waterproof sheath layer masterbatch prepared in this comparative example is re-melted and extruded in an extruder at 170-190°C and evenly extruded onto the non-woven fabric layer, and after cooling, a waterproof sheath layer coaxially and tightly wrapped with the non-woven fabric layer is formed. The internal layer structure of the prepared cable is shown in the attached figure. Figure 1 shown.

[0083] The waterproof and moisture-proof cables obtained in the above-mentioned embodiments and comparative embodiments were respectively subjected to waterproof tests, and the test operation was as follows:

[0084] The processed waterproof and moisture-proof cable is cut to obtain a 80 cm long straight section as the sample 10 (the cut surface is kept flush and parallel to the radial direction of the cable), and both ends of the axial direction of the sample 10 are exposed. The sample 10 is placed in the center of the water storage tank 20 along the horizontal straight line in the left and right directions of its own length (the inner cavity (water storage cavity) of the water storage tank 20 is a rectangular space with a right-set length of 50 cm in the left and right directions, a width of 30 cm in the front and back directions, and a height of 60 cm. In the water storage cavity, the height of the bottom of the sample 10 from the bottom of the cavity is 10 cm). The sample 10 passes through the wall of the water storage tank 20 and is fixedly installed on the water storage tank 20 along its own axial direction. Both ends of the sample 10 extend horizontally outward from the water storage tank 20, and the exposed surface of one end of the sample 10 located outside the water storage tank 20 in the axial direction is stably connected to the humidity sensor 40 for detection (the detection end of the humidity sensor 40 is stably contacted with the non-woven fabric layer 4 on the exposed cross section of the sample 10. This is because the non-woven fabric layer 4 itself has water permeability, so once the outermost waterproof sheath layer 6 is penetrated by water, the penetrated water will also migrate through the non-woven fabric layer 4 and contact the detection end of the humidity sensor 40), and the exposed surface of the other end is sealed with a flexible waterproof film and a rubber band. The entire test device is located in a stable constant temperature and humidity (30°C, relative humidity 30%) air-conditioned room, as shown in the attached Figure 2 At this time, the humidity sensor 40 will gradually stabilize to an initial value (about 30%), which is caused by the environmental humidity and the environmental humidity affecting the exposed surface of the sample 10.

[0085] After the above installation operation is completed, water is added to the water storage chamber until the water surface is 30 cm above the top of the sample 10, thereby forming a continuous water pressure on the sample 10, and the water temperature is 30°C (the top of the water storage chamber cannot be completely sealed by covering the box cover 21, so that the water storage chamber is connected to the ambient atmospheric pressure), and the timing is started. Every 12 hours, the humidity change displayed by the humidity sensor 40 connected to the exposed surface detection of the sample 10 is observed to determine whether the water in the water storage tank 20 penetrates through the outermost waterproof sheath layer of the sample 10 and enters the cable to reach the exposed surface. (Fully taking into account the fluctuation of environmental humidity) When the humidity value displayed on the humidity sensor 40 is observed to exceed 10% of the initial value for two consecutive times, it is considered that the outermost waterproof sheath layer of the sample 10 has been obviously penetrated by water, and the infiltrated water penetrates and migrates to the exposed cross section inside the cable sample 10, causing the humidity at the exposed cross section to increase significantly. The test is completed and the test duration is recorded (based on the previous observation time of "the humidity value is observed to exceed 10% of the initial value for two consecutive times". Three samples are measured for the same item and the average is taken). The details are shown in Table 1.

[0086] Table 1

[0087]

[0088] (The "tensile strength" and "elongation at break" in Table 1 are obtained by testing the waterproof sheath layer in accordance with the standard GB / T 2951 "General test methods for insulation and sheath materials of electric and optical cables". Three samples are tested for the same item and the average is taken.)

[0089] In Table 1, Comparative Examples 1 to 5 are obtained by changing Example 1, wherein the applicant believes that, compared with Comparative Example 1, after the introduction of the cation-doped resin rich in benzene ring side groups, due to compatibility issues, this part of the cation-doped resin will precipitate and migrate to a position relatively close to the surface of the sheath, and more negatively charged fluorine segments will also approach and aggregate to the surface of the sheath through the charge carried by the cations, thereby further reducing the surface energy of the sheath surface, making the waterproof property more ideal, and the water blocking time in the test longer.

[0090] Comparative Example 2 is compared with Example 1, in which no fluorine resin modification is added, and the cation-doped resin still migrates to a position relatively close to the surface of the sheath. Although the benzene ring on the cation-doped resin is a hydrophobic group, the cations carried by the doped resin are hydrophilic, and the final combined waterproof and water-resistant effect is very unsatisfactory. In fact, the applicant believes that the cations close to the surface of the sheath in Example 1 themselves will also reduce the waterproof effect, but these cations attract more fluorine segments through the action of charge, and show a more obvious hydrophobic effect near the surface of the sheath, which ultimately improves the waterproof effect.

[0091] In Comparative Example 3, the introduced doped resin does not contain cations and cannot provide charge attraction for the fluorine segments; and the applicant also believes that the doped resin carries a large number of large-volume benzene ring side groups. After the doped resin migrates to a position relatively close to the sheath surface, it blocks a part of the fluorine segments from approaching the sheath surface. Therefore, the water repellent effect of Comparative Example 3 is reduced compared to Comparative Example 1 without any doped resin. In fact, the applicant believes that the doped resin containing cations in Example 1 will also block the fluorine segments from approaching the sheath surface based on the presence of benzene rings, but the charge attraction of the cations is more obvious. In summary, more fluorine segments are "out of the box" from the polypropylene matrix and approach and aggregate to the sheath surface, so the water repellent performance is improved.

[0092] Comparative Example 4 Compared with Example 1, the applicant believes that after the benzene ring content on the cation-doped resin in Comparative Example 4 is further increased to a certain extent, the steric hindrance effect caused by the benzene ring on the cation-doped resin close to the sheath surface also increases accordingly, and the blocking effect on the fluorine chain segment becomes more and more obvious, resulting in only fewer fluorine chains being attracted by the cationic charge close to the sheath surface compared to Example 1, resulting in a decrease in the water-repellent effect compared to Example 1.

[0093] In Comparative Example 5, after the benzene ring content on the cation-doped resin was significantly reduced, the compatibility between the doped resin and the matrix resin polypropylene was significantly improved compared with Example 1. Therefore, the amount of cation-doped resin migrating to the surface of the sheath was also reduced accordingly. Although the steric effect on the fluorine segment was also weakened, on the one hand, the charge attraction of the sheath surface to the fluorine segment was also reduced. Moreover, the part of the cations originally close to the sheath surface is now relatively dispersed in the sheath matrix. After the fluorine segment is attracted in the matrix, it also inhibits the migration and aggregation of the fluorine segment to the surface of the sheath. Therefore, the final waterproof effect is also significantly reduced.

[0094] In summary, compared with the destruction of the hydrophobic effect by the cations that migrate close to the sheath surface, and the steric hindrance of the large-volume side benzene rings (when the number is controlled at a certain level) to the migration of the fluorine chain segments to the sheath surface, the charge attraction of the cation positive charge on the fluorine chain segments is truly decisive.

Claims

1. A waterproof and moisture-proof cable with a simple layer structure, characterized in that: The waterproof and moisture-proof cable comprises two or more conductor cores (1), each of the conductor cores (1) being tightly wrapped with an insulating layer (2), each of the insulating layers (2) being tightly wrapped with a shielding layer (3), all of the conductor cores (1) wrapped with the insulating layer (2) and the shielding layer (3) being twisted together as a whole and tightly wrapped by a non-woven fabric layer (4), and the non-woven fabric layer (4) being tightly wrapped with a waterproof sheath layer (6), The waterproof sheath layer (6) comprises, by weight, 100 parts of polypropylene, 10-15 parts of POE thermoplastic elastomer, 10-20 parts of fluororesin, 5-10 parts of cationic doped resin, 3-8 parts of plasticizer, 1-2 parts of antioxidant, and 1-3 parts of lubricant.

2. The waterproof and moisture-proof cable with a simple layer structure as claimed in claim 1, characterized in that: The conductor core (1) is formed by twisting a plurality of round copper wires.

3. The waterproof and moisture-proof cable with a simple layer structure as claimed in claim 1, characterized in that: The aluminum-plastic tape is evenly wrapped around the insulating layer (2) to serve as the shielding layer (3).

4. The waterproof and moisture-proof cable with a simple layer structure as claimed in claim 1, characterized in that: The non-woven fabric is evenly wrapped around the conductor core (1) whose surface is sequentially wrapped with the insulating layer (2) and the shielding layer (3) and twisted together to serve as the non-woven fabric layer (4).

5. The waterproof and moisture-proof cable with a simple layer structure as claimed in claim 1, characterized in that: The inner side of the non-woven fabric layer (4) and the gap between the conductor cores (1) wrapped with the insulating layer (2) and the shielding layer (3) are filled with a filling rope (5).

6. The waterproof and moisture-proof cable with a simple layer structure as claimed in claim 1, characterized in that: The cationic doped resin is polymerized from butyl acrylate, styrene and a cationic monomer, wherein the cationic monomer is methacryloyloxyethyl trimethylammonium chloride, and the weight ratio of the butyl acrylate, the styrene and the cationic monomer is 40-60:40-60:10-15.

7. The waterproof and moisture-proof cable with a simple layer structure as claimed in claim 6, characterized in that: The preparation process of the cation-doped resin is as follows: (1) After the cationic monomer is fully dispersed and dissolved in water, the butyl acrylate and the styrene are added dropwise thereto under stirring. After the addition is completed, stirring is continued until the emulsification is fully emulsified to form an emulsion, and two-thirds of the emulsion is taken out for subsequent addition; (2) Under condensation reflux, the remaining one third of the emulsion in step (1) is heated in a water bath to 70-80° C. under stirring, and an initiator solution is added thereto. After a period of time, another two thirds of the emulsion taken out in step (1) is added thereto. After the addition of the initiator solution and the emulsion is completed, the reaction is continued at a temperature of 1° C. for a period of time, and then the temperature is cooled to room temperature. The obtained reaction system is centrifuged, and the obtained polymer is fully washed and dried.

8. The waterproof and moisture-proof cable with a simple layer structure as claimed in claim 1, characterized in that: The fluororesin is polyvinylidene fluoride.

9. The waterproof and moisture-proof cable with a simple layer structure as claimed in claim 1, characterized in that: The plasticizer is dibutyl phthalate or dioctyl phthalate; the antioxidant is antioxidant 1010 or antioxidant 168; and the lubricant is zinc stearate or calcium stearate.

10. The waterproof and moisture-proof cable with a simple layer structure as claimed in claim 1, characterized in that: The processing method of the waterproof and moisture-proof cable comprises: melting the insulating layer masterbatch in an extruder, extruding it onto the outer surface of the conductor core (1), and cooling to form the insulating layer (2) tightly wrapped on the conductor core (1); wrapping the aluminum-plastic tape evenly and tightly on the insulating layer (2) as the shielding layer (3); twisting all the conductor cores (1) wrapped with the insulating layer (2) and the shielding layer (3) together, and evenly wrapping them with non-woven fabric to form the non-woven fabric layer (4); melting the masterbatch for preparing the waterproof sheath layer (6) in an extruder, extruding it onto the non-woven fabric layer (4), and cooling to form the waterproof sheath layer (6) tightly wrapped on the non-woven fabric layer (4).